Hard Time: A Content Analysis of Incarcerated Women's Personal Accounts. Issue 1 (February 2018) - Casey, Rachel C.
As the number of women incarcerated in the United States continues to rise and their complex needs become more apparent, social workers must fortify their historical commitment to criminal justice reform. However, crafting more effective and compassionate responses to the needs of justice-involved women may very well require a more nuanced understanding of the holistic impact of incarceration on women's well-being than the current literature offers. Utilizing the framework of feminist standpoint epistemology, the researcher engaged in qualitative content analysis to examine published personal accounts from 43 women to better understand their experiences in prisons and jails in the United States. Two overarching themes emerged from the analysis. First, the personal accounts illustrated that women experience prisons and jails as environments of denial insofar as these carceral environments deny women's basic needs, their sense of humanity, and their personal power. The second overarching theme pertains to the holistic impact of the carceral environment upon women's lives, meaning it has expansive effects on women's biopsychosocial–spiritual functioning. Social workers should dedicate efforts to dramatically reducing the number of women behind bars and engaging in holistic intervention approaches that might counteract the negative effects of incarceration across domains of well-being.